Assessment of COX-2 expression presence and severity by immunohistochemical method in patients with chronic active gastritis and intestinal metaplasia - Gülbanu ERKAN; İpek Işık ERKAN and Uğur KANDİLCİ and Ayşe DURSUN (Turkish Journal of Gastroenterology, 2019)
-